The missing term in the simlified expression s -2
Expressions are mathematical statements that involve numbers and variables
Represent the missing term in the expression with y.
So, the equation that relates both expressions is:
[tex]-46x + 18 = y - 4(12x -5) + 2x[/tex]
Open the bracket
[tex]-46x + 18 = y - 48x +20 + 2x[/tex]
Collect like terms
[tex]-46x + 18 = y - 46x +20[/tex]
Add 46x to both sides
[tex]18 = y +20[/tex]
Subtract 20 from both sides
[tex]y = -2[/tex]
Hence, the missing term is -2
Read more about expressions at:
https://brainly.com/question/4344214